A taxonomic revision of Silene nocturna species complex (Caryophyllaceae) in Italy - Peruzzi, Lorenzo; Carta, Angelino (Phytotaxa, 2013)
The taxonomy of the closely related Silene capraria, S. neglecta and S. nocturna in Italy is investigated, by means of morphometric and karyological analyses. The chromosome numbers of S. capraria and S. neglecta (both diploid with 2n = 24) are here reported for the first time. On the basis of the morphological results, we propose the species rank for S. neglecta, and to consider S. capraria as a vicariant narrow endemic subspecies of the widespread S. nocturna. The name S. neglecta is lectotypified on a specimen preserved in the Herbarium Tenore at NAP. With the aim to distinguish these taxa, the useful qualitative and quantitative morphological characters are highligthed.